Angiotensin II modulates glutamate-induced depolarizations and synaptic transmission in rat locus coeruleus neurons in vitro. - Xiong, Huangui. (University of Ottawa (Canada), 1993)
Considerable evidence now supports a neurotransmitter or neuromodulatory role for angiotensin II (AII) in the central nervous system (CNS). The objectives of this research are to study the actions of AII on spontaneous activity and on Glu-induced responses in rat locus coerulus neurons. The action of AII appears to be selective since it had no effect on the depolarizations evoked by acetylcholine (ACh), or by depolarizing current injections. Selectivity is also indicated by the observation that AII had little or no effect on Glu responses in brain stem neurons outside of the LC where AII receptors have not been reported to be present. AII was also found to be subject to rapid peptidase degradation. When AII was applied by bath perfusion, rather than by iontophoretic or pressure application, it had little or no effect on Glu responses. However, when Sar$\sp1$-AII, an analogue which is resistant to aminopeptidase degradation was bath-applied, or when AII was applied together with peptidase inhibitors, the depressant action on Glu responses was observed. Like AII, angiotensin III (AIII) also had depressant actions on Glu responses in LC neurons, but the action of AIII appeared to be less potent than that of AII. In addition to its strong depressant actions on applied Glu-induced responses, AII was also found to depress responses to synaptically released excitatory amino acids (EAAs). In fact we were able to show that excitatory postsynaptic potentials (EPSPs) evoked by electrical stimulation were blocked by Glu receptor antagonists, indicating involvement of EAAs in the mediation of the EPSPs. Sar$\sp1$-AII or AII applied together with peptidase inhibitors depressed the amplitudes of the EPSPs in a concentration dependent manner. The depressant actions of AII on EPSPs were also antagonized by the AT$\sb2$-selective antagonist PD123177, indicating again the involvement of AT$\sb2$ receptors in the mediation of AII action on EAA-induced responses. The functional significance of the depressant action of AII on Glu responses in the LC neurons is at present unclear. It may represent a role for a brain angiotensinergic system in control of cardiovascular functions through modulation of the actions of excitatory amino acid neurotransmitters on LC neuronal activity. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.